Eye-masks and earplugs compared to headband in nulliparas on increasing spontaneous vaginal delivery: a randomized trial - Jesrine Gek Shan Hong; Annamalai Vimaladevi; Noor Adeebah Razif; Siti Zawiah Omar; Peng Chiong Tan (BMC, 2023)
Abstract Background A majority of pregnant women experience sleep disruption during pregnancy, especially in the third trimester. Lack of sleep is associated with preterm birth, prolonged labor and higher cesarean section rate. Six or less hours of night sleep in the last month of pregnancy is associated with a higher rate of caesarean births. Eye-masks and earplugs compared to headband improve night sleep by 30 or more minutes. We sought to evaluate eye-mask and earplugs compared to sham/placebo headbands on spontaneous vaginal delivery. Methods This randomized trial was conducted from December 2019-June 2020. 234 nulliparas, 34-36 weeks' gestation with self-reported night sleep < 6 h were randomized to eye-mask and earplugs or sham/placebo headband (both characterized as sleep aids) to be worn each night to delivery. After two weeks, interim outcome data of the average night sleep duration and the trial sleep related questionnaire was answered through the telephone. Results Spontaneous vaginal delivery rates were 60/117(51.3%) vs. 52/117(44.4%) RR 1.15 95% CI 0.88-1.51 P = 0.30 for eye-mask and earplugs or headband respectively. At 2-weeks into the intervention period, the eye-mask and earplugs arm reported longer night sleep duration 7.0 ± 1.2 vs. 6.6 ± 1.5 h P = 0.04, expressed increased satisfaction with the allocated aid 7[6.0-8.0] vs. 6[5.0-7.5] P < 0.001, agreed they slept better 87/117(74.4%) vs. 48/117(41.0%) RR 1.81 95% CI 1.42-2.30 NNTb 4 (2.2-4.7) P < 0.001 and higher compliance median[interquartile range] 5[3-7] vs. 4[ 2-5] times per week of sleep aid use P = 0.002. Conclusion Eye-mask and earplugs use at home in late third trimester do not increase the spontaneous vaginal delivery rate even though self-reported night sleep duration, sleep quality, satisfaction and compliance with allocated sleep aid were significantly better than for sham/placebo headband. Trial registration This trial was registered with ISRCTN on June 11, 2019 with trial identification number: ISRCTN99834087 .